Multiattribute decision making based on the binary connection number in set pair analysis under an interval-valued intuitionistic fuzzy set environment - Shen, Qing; Huang, Xu; Liu, Yong; Jiang, Yunliang; Zhao, Keqin (Soft computing (Berlin, Germany), 2020)
A new multiattribute decision-making (MADM) methodology based on set pair analysis (SPA) for an interval-valued intuitionistic fuzzy set environment is developed in this paper. The connection number, which is known as a major component of SPA, provides a quantitative analysis to integrate the certainty and uncertainty as a combined system. First, we briefly review the concepts of interval-valued intuitionistic fuzzy sets (IVIFS) and the binary connection number (BCN). Then, the transformation method of interval-valued intuitionistic fuzzy numbers into BCNs is studied. Finally, we present a new MADM method where interval-valued intuitionistic fuzzy values are used to express evaluating values of alternatives on attributes, and weights are represented with real numbers or IVIFS. Some typical examples are presented to illustrate the feasibility and validity of the proposed approach.